Revitalisasi Peran Kantor Urusan Agama dalam Pembinaan Keluarga Sakinah di Kota Palopo Perspektif Maqãshid Al-Syari’ah - Jamin, Ummu Akalsum; Rahmawati; Kaddase, Muh. Thayyib (Palita: Journal of Social Religion Research, 2024)
This study aims to determine the role of the Religious Affairs Office (KUA) in fostering a sakinah family in Palopo City, analyze the obstacles faced, and examine the revitalization of the role of the KUA in the perspective of Maqāshid al-Syarī'ah. This research uses qualitative methods (field research) with juridical, sociological, and normative approaches. Data collection techniques include observation, interviews, and documentation, then analyzed descriptively qualitatively. The results showed that the role of the KUA in fostering a sakinah family includes coaching and monitoring prospective brides, marriage services and administration, and providing premarital guidance. The obstacles faced by the KUA in Palopo City include limited professional human resources, inadequate facilities, lack of training related to family development, and mismatch between the educational background of employees and their duties. In addition, the community's low understanding of the importance of marriage guidance is also a significant obstacle. Revitalizing the role of the KUA in fostering a sakinah family does not contradict the principles of Maqāshid al-Syarī'ah, especially in the aspects of preserving religion, offspring, soul, mind, and property. Through marriage guidance, communication within the family, and conflict resolution based on religious values, the KUA contributes to the realization of sakinah, mawaddah, and rahmah families as well as maintaining the quality of generations and overall family welfare.   Keywords: Religious Affairs Office, Family Development, Maqāshid al-Syarī'ah, Palopo City